2006
DOI: 10.1016/j.virol.2005.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The infectivity and host range of the ecotropic porcine endogenous retrovirus, PERV-C, is modulated by residues in the C-terminal region of its surface envelope protein

Abstract: Endogenous retroviral genetic material serves as a reservoir for the generation of retroviral pathogens by recombination between activated endogenous or exogenous infectious agents. Some porcine tissues actively express infectious porcine endogenous retroviruses (PERVs). Of the three classes of PERV characterized to date, two, PERV-A and B, are capable of infecting human cells in vitro, whereas PERV-C cannot. Here, we demonstrate that the PERV-C envelope surface protein (SU) when disassociated from its C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 32 publications
0
54
0
Order By: Relevance
“…Notably, we find that binding to the BLV receptor did not require the presence of immediately downstream PRR sequences of BLV Env. This is of particular importance since, in the context of HTLV, retroviral PRR or downstream sequences may bind to cell surface components other than the primary receptor (45,46), and sequences outside the RBD in some gammaretrovirus SU appear to modulate or block binding and infection (47)(48)(49). Nevertheless, in the context of the BLV envelope, an Env-specific binding interference assay demonstrated that the BLV RBD alone decreased B RBD binding to levels similar to that detected in the presence of the entire BLV Env.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we find that binding to the BLV receptor did not require the presence of immediately downstream PRR sequences of BLV Env. This is of particular importance since, in the context of HTLV, retroviral PRR or downstream sequences may bind to cell surface components other than the primary receptor (45,46), and sequences outside the RBD in some gammaretrovirus SU appear to modulate or block binding and infection (47)(48)(49). Nevertheless, in the context of the BLV envelope, an Env-specific binding interference assay demonstrated that the BLV RBD alone decreased B RBD binding to levels similar to that detected in the presence of the entire BLV Env.…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that PERV-C RBD can bind human cells specifically, in a dosedependent manner (Gemeniano, Mpanju et al 2006). More recently, we demonstrated that relatively few amino acid changes in the PERV-C envelope can allow infection of human cells (Argaw, Figueroa et al 2008).…”
Section: Perv Envelopementioning
confidence: 88%
“…Harrison et al used a naturally occurring recombinant of PERV-A and PERV-C with high titer on human cells compared to parental PERV-A and showed two regions that correlated with increased infection on human cells: amino acid residue 140 that lies between VRA and VRB and additional sequences within the PRR (Harrison, Takeuchi et al 2004). Our laboratory has also shown that sequences within the C-terminal region of the SU influence human cell infectivity (Gemeniano, Mpanju et al 2006;Argaw, Figueroa et al 2008).…”
Section: Perv Envelopementioning
confidence: 95%
See 1 more Smart Citation
“…In addition, there are also other reasons not to use PERV-C positive animals. First, the ability of PERV-C to infect cells that do not harbor the specific receptor by receptor-independent infection (Lavillette and Kabat, 2004), and second, mutations in the envelope protein of PERV-C may change the tropism towards human cells (Gemeniano et al, 2006). These data indicate, that breeding out PERV-C will reduce the risk of PERV transmission in xenotransplantation.…”
Section: Discussionmentioning
confidence: 99%